Joomla! explained : your step-by-step guide - Burge, Stephen , 1978- (Addison-Wesley, 2012)
Joomla! now powers tens of millions of websites of every size and type. But many beginners find it confusing. Burge teaches everything beginners need to know-- and nothing they don't need to know!